Not in vain ; 20th what God hath wrought amongst the Kanakas being Report of the Solomon Island Branch and Twentieth annual report of the Queensland Kanaka Mission for the year 1905-1906 (1906)
Contents includes : Queensland Kanaka Mission : Object and principles (revised).
Photocopy.
Keywords: Queensland Kanaka Mission; Queensland Kanaka Mission Solomon Island Branch; Brethren movement -- missions -- Australia -- history